FESTIVAL DE INVERNO OF UFPR: METHODOLOGICAL WAYS OF AN EXTENSION PROJECT (Fiep Bulletin - online, 2015)
The present text aims to tell the metodological ways of the project intitled “TEMPO DE BRINCAR NA PRAÇA”, developed in the XV Festival de Inverno of UFPR in Antonina/PR, on 2005. This action took care of 200 professors of the Municipal Network of Education and aproximately 300 children/day at the age of 06 to 14 years old.  Co-ordinated by Teachers of the Departamento de Educação Física, assisted by scholarship holders of the CEPELS/UFPR. This intervention consolidated itslef while extension project, whit practical interventions, in the scope of the leisure-education. Considering the leisure as the culture  understood in it  wide sense  lived (practised or enjoyed) in the conquered time, some contents of the corporal culture was developed, extended and transformed.
Keywords: Physical Education; Leisure; Culture.